Body actions - Rotner, Shelley; White, David A., (David Alan), 1973- (New York : Holiday House, 2012)
Introduces the nervous, skeletal, muscular, respiratory, and circulatory systems and major organs through illustrations of children running, jumping, riding bikes, and using all five senses and explanatory overlays.
3.6
K-3
Keywords: Human body -- Juvenile literature; Human body; Human body; Human anatomy; Picture books for children